Live-Attenuated VEEV Vaccine Delivered by iDNA Using Microneedles Is Immunogenic in Rabbits - Tretyakova, Irina; Tomai, Mark; Vasilakos, John; Pushko, Peter (Frontiers in Tropical Diseases, 2022)
Effective and simple delivery of DNA vaccines remains a key to successful clinical applications. Previously, we developed a novel class of DNA vaccines, sometimes called iDNA, which encodes the whole live-attenuated vaccine viruses. Compared to a standard DNA vaccine, an iDNA vaccine required a low dose to launch a live-attenuated vaccine in vitro or in vivo. The goal of this pilot study was to investigate if iDNA vaccine encoding live-attenuated Venezuelan equine encephalitis virus (VEEV) can be efficiently delivered in vivo by a microneedle device using a single-dose vaccination with naked iDNA plasmid. For this purpose, we used pMG4020 plasmid encoding live-attenuated V4020 vaccine of VEE virus. The V4020 virus contains structural gene rearrangement, as well as attenuating mutations genetically engineered to prevent reversion mutations. The pMG4020 was administered to experimental rabbits by using a hollow microstructured transdermal system (hMTS) microneedle device. No adverse events to vaccination were noted. Animals that received pMG4020 plasmid have successfully seroconverted, with high plaque reduction neutralization test (PRNT) antibody titers, similar to those observed in animals that received V4020 virus in place of the pMG4020 iDNA plasmid. We conclude that naked iDNA vaccine can be successfully delivered in vivo by using a single-dose vaccination with a microneedle device.